Non-rigid registration of breast images using feature points. - Zhang, W; Wessel, C; Ho, C; Brady, M (2010)
We present a feature point detection algorithm which we use for non-rigid registration, illustrated for breast images (mammography, MRI). By associating the continuous intrinsic dimensionality of image structure with the output of a scale saliency algorithm, breast boundary points can be separated from internal feature points. Correspondences established for the breast boundary and internal feature points respectively are used to drive two recent non-rigid registration techniques: polyaffine transformation and coherent point drift registration. Experimental results are presented for digital breast tomosynthesis and 3D breast MRI, and in all case achieve good spatial alignments.